Carbon fluxes from plants to soil and dynamics of microbial immobilization under plastic film mulching and fertilizer application using 13C pulse-labeling. (January 2015) - An, Tingting; Schaeffer, Sean; Li, Shuangyi; Fu, Shifeng; Pei, Jiubo; Li, Hui; Zhuang, Jie; Radosevich, Mark; Wang, Jingkuan
Abstract: Plastic film mulching and fertilizer application have improved soil fertility and sustainable agricultural development in China. However, there is limited information on carbon (C) fluxes from plants to soil, and dynamics of microbial immobilization where these practices have been employed. The objectives of this study were to quantify the photosynthesized C transported from maize to soil, and to assess the effect of mulching (with or without plastic film mulching) and fertilizer (no fertilizer control, medium-level organic manure, and high-level organic manure) application on the dynamics of microbial C sequestration. We used in-situ 13 C pulse-labeling of maize planted at an experimental site in Liaoning Province, China. We found, on average, from 12% to 15% of net fixed 13 C was translocated belowground up to 15 days after labeling. More than 60% of 13 C retained in soil was incorporated into microbial biomass C on the 1st day, but only less than 27% on the 15th day after labeling. Treatments that combined organic manure application with mulching showed the greatest proportion of photosynthesized 13 C incorporated belowground and the largest amount of microbial biomass C derived from rhizodeposits. These results demonstrate that organic manure application coupled with plastic film mulching facilitates photosynthesized C sequestration belowground and enhances soil microbial activity during the maize seedling stage. Highlights: Microbial C immobilization under organic manure amendment and plastic mulching. In-situ 13 C pulse labeling of maize seedlings and measurement after 15 days. Manure with mulching increase plant C input to rhizosphere and soil. Manure and mulching increase 13 C-microbial biomass C in rhizosphere and bulk soil. Manure and mulching affect microbial dynamics, increasing soil C sequestration.